THE EFFECT OF ENTERPRISE RISK MANAGEMENT DISCLOSURE, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, AND PROFITABILITY ON THE VALUE OF MANUFACTURING COMPANIES LISTED ON THE IDX FOR THE YEAR 2019-2020 - Steven Jonathan; Temy Setiawan (INQUISITIVE : International Journal of Economic, 2022)
In making investment decisions, of course, investors must pay attention to financial and non-financial aspects. In the financial aspect, of course, it can be seen through the level of company profitability. Meanwhile, in the non-financial aspect, potential investors can use the company's non-financial information such as corporate risk management and corporate social responsibility. This study aims to provide empirical evidence of the influence of financial aspects, namely profitability and also the influence of non-financial aspects, namely corporate risk management and corporate social responsibility on firm value. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2020 period as many as 172 companies. The sampling technique in this study used a purposive sampling technique so that 95 data were obtained from the company's annual report. Analysis using SPSS program with multiple linear regression analysis method. This study provides empirical evidence that the financial aspect, namely profitability, has a positive influence on firm value. Then the non-financial aspect, namely corporate social responsibility, also has a positive influence on firm value, while corporate risk management has no effect on increasing firm value. This study provides information to potential investors that to assess the company can be seen from the financial and non-financial side. This encourages companies to better disclose non-financial information in order to have a positive impact on the company and external parties in need.